Approach to Contextual Models in Improving Learning Education in Citizenship at 5’th Grade Cugenang Public Elementary School - Parhan, Muhamad (Universitas Pendidikan Indonesia, 2019)
This research attempts to recontruct Learning Citizenship Education (PKn) fifth grade (5â€™th grade) SDN Cugenang (elementary school) still have not capable of being belonging to school tuition and can be apply in real life. Learning that takes place still puts forward a form of learning theoretical-abstract by presenting a set of the theory, symbol, textual and skriptual containing a number of fact, the concept and principle that is rote and knowledge. Referring to the condition of the research aims to understand lessons with the approach model contextual in learning citizenship education (PKn). In a research the act of classroom action research with four the stage of activity that is: planning, the act or, observation and reflection, done as many three cycles. Technique data collection out by means of: observation, interview, documentation and chief. This research showed that learning citizenship education (PKn) with the approach contextual make processes and results learning is better and more robust.Â Keywords: Model, Contextual, Citizenship Education